PERFIL EPIDEMIOLÓGICO DA SÍNDROME DE GUILLAIN BARRE NO MUNICÍPIO DE IJUÍ-RS - BONAMIGO, ELENITA C. B.; COSTA, MARLUI M. D.; NASCIMENTO, LIBERA M.; RUTZEN, VANISE M. (Salão do Conhecimento, 2013)
Resumo